2007
DOI: 10.5144/0256-4947.2007.183
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Compartment Syndrome

Abstract: The term abdominal compartment syndrome (ACS) describes the clinical manifestations of the pathologic elevation of the intra-abdominal pressure (IAP). When the IAP exceeds 12 mm Hg it is referred to as intra-abdominal hypertension (IAH) while ACS generally sets in at an IAP in excess of 20 mm Hg. This syndrome is most commonly observed in the setting of severe abdominal trauma and in the aftermath of major abdominal operations. ACS affects mainly the respiratory, cardiovascular, renal, gastrointestinal and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…In patients suspected to have elevated IAP, routine monitoring is advocated. However, these patients often have common risk factors for ACS, such as trauma, massive hemorrhage, or protracted volume resuscitation situations [ 2 ]. Intra-abdominal malignancies are a less common cause of ACS, and thus routine monitoring of IAP is not routinely done and is highly dependent on physician judgment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients suspected to have elevated IAP, routine monitoring is advocated. However, these patients often have common risk factors for ACS, such as trauma, massive hemorrhage, or protracted volume resuscitation situations [ 2 ]. Intra-abdominal malignancies are a less common cause of ACS, and thus routine monitoring of IAP is not routinely done and is highly dependent on physician judgment.…”
Section: Discussionmentioning
confidence: 99%
“…There is a relative paucity of literature on ACS in children compared to adults and even less describing ACS in pediatric oncologic patients. Studies have shown that adverse effects of elevated IAP occur at lower levels than previously thought, which may be difficult to measure, and can manifest suddenly as fulminant ACS, especially in patients with intra-abdominal malignancies [ 2 ]. In particular, pediatric patients with large abdominal malignancies do not show obvious early symptoms, and many are also unable to complain about the increasing physical discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal compartment syndrome (ACS) is characterized by intra-abdominal hypertension (IAH), elevation and splinting of the diaphragm, high pleural pressure, and poor venous return to the heart, producing low cardiac output and shock which, in turn, results in poor venous return across the capillaries setting a vicious cycle. ACS and IAH affect all body systems, most notably the circulatory, respiratory, urinary and nervous [ 1 ].…”
Section: Introductionmentioning
confidence: 99%